Vapor Transport Deposition Technology for Perovskite Films - Da‐chang Liu (Advanced Materials Interfaces, 2025)
Abstract The power conversion efficiency of metal halide perovskite solar cells (PSCs) has achieved parity with that of crystalline silicon photovoltaic devices, necessitating large‐scale industrial production for their commercial viability. Vapor deposition technology is deemed the most viable method due to its controllability and high repeatability. However, its application is constrained by a low deposition rate and high cost. The introduction of vapor transport deposition (VTD) technology aims to address these limitations and facilitate the mass production of perovskite devices. Herein, the technical characteristics, development history, and research progress of VTD in the perovskite field are briefly analyzed, and insights into potential challenges and prospects are put forward. The development of VTD technology is believed to promote the commercialization process of PSCs.